Strategi Komunikasi Pemerintah Kabupaten Bener Meriah dalam Pemasaran Kopi Gayo dan Pemberdayaan Masyarakat - Nurul Khansa Fauziyah; Aini Mahara (UIN Raden Mas Said Surakarta, 2022)
Communication strategy of the Bener Meriah Regency Government in the marketing of Gayo coffee. The problems of this study are; how the communication strategy of the Bener Meriah Regency Government in marketing Gayo coffee, how the obstacles of the Bener Meriah Regency government in marketing Gayo coffee, how the credibility of communicators in marketing Gayo coffee, and local community empowerment in gayo coffee marketing. The research method in this study uses qualitative research approach, using observation, interview and point documentation techniques. In this study, the authors use the theory of communicator credibility. The results of this study are the communication strategy of the Bener Meriah Regency government in marketing Gayo coffee using the methods; marketing communication strategy through advertising in exhibitions and events, through foreign trade missions by ministries, and promotions through digital processes and social media. The credibility of the communicator in marketing Gayo coffee is good enough to increase sales, so that Gayo coffee can be well-known to foreign countries. The government’s effort to appreciate marketing communicators have also been quite good, so that communicators are more enthusiastic and creative. Barriers to the government of Bener Meriah Regency in marketing Gayo coffee are (1) Barriers to entering the industrial market, (2) Inadequate facilities and technology, (3) Barriers in regulations, especially employment, taxation and trade, (4) Lack of motivation and trade, (5) Low capital, (7) Processing and packaging technology that has not been fully mastered. The Bener Meriah Regency Government has carried out community empowerment by utilizing its natural resources, providing assistance in the form of directions, outreach, and training on Gayo coffee management.